2020
DOI: 10.1017/s1431927620017900
|View full text |Cite
|
Sign up to set email alerts
|

RFP-tagged Hongotoxin 1 and Its Interactions with KscA-Kv1.1 Hybrid Channels

Abstract: This is an Accepted Manuscript for the Microscopy and Microanalysis 2020 Proceedings. This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Notably, AgTx-2 with GFP at its N-terminus exhibits high specificity for chimeric K V 1.3 channels over K V 1.1 and K V 1.6 in spheroplasts, and KcsA-K V 1.3 transfected HEK293 cells [ 62 ]. Similar studies with the fusion of HgTx with Tag-RFP showed maintained specificity and utility for targeting KcsA-K V 1.1 [ 63 ] as well as both KcsA-K V 1.1 and KcsA-K V 1.3 [ 64 ]. Finally, GFP-MgTx fusion protein revealed specific labelling of the K V 1.3 subunits of the KcsA-K V 1.3 hybrid channels expressed in E. coli spheroplasts, whilst control experiments with non-transfected material showed no fluorescence signal [ 65 ].…”
Section: Optical Probes Targeting Potassium Channelsmentioning
confidence: 87%
“…Notably, AgTx-2 with GFP at its N-terminus exhibits high specificity for chimeric K V 1.3 channels over K V 1.1 and K V 1.6 in spheroplasts, and KcsA-K V 1.3 transfected HEK293 cells [ 62 ]. Similar studies with the fusion of HgTx with Tag-RFP showed maintained specificity and utility for targeting KcsA-K V 1.1 [ 63 ] as well as both KcsA-K V 1.1 and KcsA-K V 1.3 [ 64 ]. Finally, GFP-MgTx fusion protein revealed specific labelling of the K V 1.3 subunits of the KcsA-K V 1.3 hybrid channels expressed in E. coli spheroplasts, whilst control experiments with non-transfected material showed no fluorescence signal [ 65 ].…”
Section: Optical Probes Targeting Potassium Channelsmentioning
confidence: 87%